Promising Thermoelectric Performance in Two-Dimensional Semiconducting Boron Monolayer - Hu, Yonglan; Li, Ding; Liu, Rongkun; Li, Shichang; Feng, Chunbao; Li, Dengfeng; Ding, Guangqian (Frontiers in Chemistry, 2021)
A heavy element is a special character for high thermoelectric performance since it generally guarantees a low lattice thermal conductivity. Here, we unexpectedly found a promising thermoelectric performance in a two-dimensional semiconducting monolayer consisting of a light boron element. Using first-principles combined with the Boltzmann transport theory, we have shown that in contrast to graphene or black phosphorus, the boron monolayer has a low lattice thermal conductivity arising from its complex crystal of hexagonal vacancies. The conduction band with an intrinsic camelback shape leads to the high DOS and a high n-type Seebeck coefficient, while the highly degenerate valence band along with the small hole effective mass contributes to the high p-type power factor. As a result, we obtained the p-type thermoelectric figure of merit up to 0.96 at 300 K, indicating that the boron monolayer is a promising p-type thermoelectric material.